Mulheres em gestação de alto risco: sentimentos, práticas de cuidado e superação das dificuldades enfrentadas - Wilhelm, Laís Antunes (2014)
A pregnancy is considered high-risk when the risk of disease or death, before or after birth, is larger than usual for the fetus and to the mother. Prenatal care requires evaluation of risk situations and readiness to identify problems in order to prevent an unfavorable outcome. This assistance has an important role in ensuring the health care of the pregnant woman and her baby, and supports the emotional demands of her. Such demands may be aggravating the risk of gestational, assuming the need for special attention with regard to the emotional aspects. Thus , this study as a research about emotional aspects of women who experienced pregnancy at high-risk and guiding research question "what feelings, care practices and overruns experienced by women who had a high-risk pregnancy?"; for that aimed to know the experiences of women who experienced a high-risk pregnancy . It is a descriptive field research with a qualitative approach. The scenarios for the development of the study will be the Santa Maria University Hospital and the homes of women who have had high-risk pregnancies. The informants in the study were ten women who experienced high-risk pregnancy. Data collection was conducted through semi-structured interviews. Data were analyzed using the proposed operative Minayo. The standards of Resolution No. 196/96 of the National Health Council, Ministry of Health, was be met. And was been approved by the Ethics Committee in Research under case No. 13178713.3.0000.5346. This research helped to identify the feelings experienced by women who lived a high-risk pregnancy. They reported fear, anxiety, sadness and happiness. In addition, the major care practices identified were the feeding, the rest and removal of stressors, originate of an informal and professional knowledge. It was also possible to know how these women overcame the difficulties faced during high risk pregnancies, through family support; health professionals; religion and faith; and the experience with optimism. When we considered the values and feelings of these women, care is characterized as humane and provides higher quality. Therefore, it is expected that this study will contribute to training of health professionals, including nurses, and that raises awareness and instigate them to practice dialogue and active listening, trying to understand the perspective of overcoming each high risk pregnancies, their abilities and achievements. Moreover, these care practices help to develop a horizontal relationship, of support and motivation for these women. In a way that these women can feel safe to experience this critical period in his life.